AB0234 Nailfold capillary (NC) evaluation in patients with anti-KU antibodies and various connective tissue diseases. (23rd January 2014) - Taraborelli, M.; Fredi, M.; Quinzanini, M.; Cavazzana, I.; Viardi, L.; Antonioli, C.M.; Tincani, A.; Franceschini, F.
Abstract : Background: Anti-Ku antibodies (anti-Ku) are frequently detected in patients with Systemic Sclerosis (SSc), Myositis or Overlap Syndromes. Raynaud's phenomenon (RP) is one of the main features associated with these antibodies. Objectives: To evaluate the involvement of the microcirculation in patients with anti-Ku. Methods: Anti extractable nuclear antigen (ENA) antibodies including anti-Ku were searched by counterimmunoelectrophoresis in our laboratory. Among the sera analyzed from 1995 to 2011, 51 resulted positive for anti-Ku.Clinical data were retrospectively obtained from clinical charts.The evaluation of microcirculation was made by NC through a stereoscopic microscope (Wild Heerbrugg M8, Leitz, Germany) and videocapillaroscopy (DS Medigroup, Italy). The patterns of capillary changes were defined according to Cutolo et al. [1] Results: Of the 51 patients with anti-Ku, clinical charts were available for 40 patients, that were included in this study.Overlap Syndrome were diagnosed in 15 patients: 11 had Polimyositis (PM) or Dermatomyositis in overlap with SSc (10 cases) or Systemic Lupus Erythematosus (SLE) (1 case). 11 patients had an undifferentiated connective tissue disease, 4 a SLE, 4 a Sjogren Syndrome, 3 a PM and 1 each had a SSc, a Rheumatoid Arthritis and an Antiphospholipid Syndrome.Anti-Ku were in association with other antinuclera specificities in 11 out of 40 sera (27%), while in 29 patients (73%) were isolated. Associated antibodies were: anti-SSA/Ro in 10 sera, anti-SSB/La in 2 and anti-Ki in 3.RP was present in 32 (80%) out of 40 patients.28 patients were studied by NC.A scleroderma pattern was present in 9 patients (32%), non specific alterations in 11 patients(39%), while 8 patients (28%) had a normal NC. Sclerodermapattern was statistically associated (p=0.001, Fisher's Exact test) with scleroderma spectrum disease (SSc or overlap including SSc). Table 1 shows the details of NC. Only 1 patients without RP referred other vascular symptoms (acrocianosis). Only 1 patient (overlap PM-SSc syndrome) out of the 40 studied experienced digital ulcers. We did not find either any association between isolated or associated anti-Ku and RP, scleroderma pattern or NC alterations. Conclusions: RP is a common feature in patients with anti-Ku and most patients present NC alterations.Non specific alterations are more common, but scleroderma pattern is present in a considerable number of patients, in particular those affected by SSc spectrum diseases, even if more rare NC alterations can be present also in patients without RP.Despite the high prevalence of NC alterations in anti-Ku patients major peripheral vascular complication such as ulcers are rare. References: Cutolo M, Sulli A, Pizzorni C, Accardo S. Nailfold videocapillaroscopy assessment of microvascular damage in systemic sclerosis.J Rheumatol 2000;27:155-60. Disclosure of Interest: None Declared